2020
DOI: 10.1371/journal.pone.0239480
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical movements of starry smooth-hound Mustelus asterias in the northeast Atlantic

Abstract: Commercial landings of starry smooth-hound Mustelus asterias in northern European seas are increasing, whilst our knowledge of their ecology, behaviour and population structure remains limited. M . asterias is a widely distributed demersal shark, occupying the waters of the southern North Sea and Irish Sea in the north, to at least the southern Bay of Biscay in the south, and is seasonally abundant in UK waters. There are no species-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
(112 reference statements)
2
4
0
Order By: Relevance
“…We also found the starry smooth‐hound to be most abundant in the winter months. Tagging studies have shown this is a highly migratory species, and consistent with our results, it has a general pattern of overwintering in the English Channel and Bay of Biscay, where pupping takes place, before spending summer months in the North Sea (Brevé et al, 2016, 2020; Griffiths et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…We also found the starry smooth‐hound to be most abundant in the winter months. Tagging studies have shown this is a highly migratory species, and consistent with our results, it has a general pattern of overwintering in the English Channel and Bay of Biscay, where pupping takes place, before spending summer months in the North Sea (Brevé et al, 2016, 2020; Griffiths et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Second, immature females may be more exposed than immature males to infective oncomiracidia of E. laevis, possibly due to differences in their spatial distribution. Information suggested by E. laevis patterns is in accordance with spatial segregation by sex demonstrated for adults of M. asterias in the Northeast Atlantic, where females disperse across a wider geographic range than males (Brevé et al, 2016(Brevé et al, , 2020Griffiths et al, 2020). Some gill monogeneans such as Mazocraes alosae and Dactylogyrus sp.…”
Section: Parasites As Potential Biological Indicatorssupporting
confidence: 79%
“…Therefore, these three helminth taxa may constitute useful tags of spatial segregation between males and females at immature stage. Despite recent studies on M. asterias distribution and the demonstration of sex-biased dispersal (Brevé et al, 2016(Brevé et al, , 2020Griffiths et al, 2020), knowledge on immatures is lacking. Predicted suitable habitats of M. asterias immatures generally coincide with those of adults but sex of immatures was not identified in available data (Brefeld and Meyer, 2018).…”
Section: Parasites As Potential Biological Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The twilight phase was excluded for this analysis to ensure that only depth during the day and night were compared. Similar methods for the classification of the vertical movements were used in Griffiths et al (2020). Based on the outcome of a two-sample Wilcoxon test, each 24-h cycle was classified as: (1) diel vertical migration (DVM), ( 2) reverse diel vertical migration (rDVM), or (3) no difference in depth.…”
Section: Vertical Movementsmentioning
confidence: 99%